Fast computation of complex error function of the real argument - Malko, S.V.; Pavlov, S.S.; Tretiak, K.K. (Вопросы атомной науки и техники, 2017)
A new efficient technique for evaluation of complex error function of the real argument on the base of the Euler-Maclaurin formula and a non-singular formula for the principal value of the Cauchy integral is given. . It is demonstrated that for the real values of argument, which are most “expensive” in the computational time, the new algorithm is almost two times faster than algorithm 680 with the same accuracy. The code was successfully implemented to ray tracing code that is used for application for investigation of ICR plasma heating in JET-type tokamaks. Предлагается новый эффективный метод вычисления комплексной функции ошибок реального аргумента на основе несингулярной интегральной формы Коши и формулы Эйлера-Маклорена. Показано, что для действительных значений аргумента, которые являются наиболее "дорогими" по времени вычислений, новый алгоритм примерно в два раза быстрее, чем алгоритм 680 с той же точностью. Алгоритм был успешно использован в коде лучевых траекторий, который применялся для исследования ИЦР-нагрева плазмы в токамаке типа JET. Пропонується новий ефективний метод обчислення комплексної функції помилок реального аргументу на основі несінгулярної інтегральної форми Коші та формули Ейлера-Маклорена. Показано, що для дійсних значень аргументу, які є найбільш "дорогими" за часом обчислень, новий алгоритм приблизно в два рази швидший, ніж алгоритм 680 з тією ж точністю. Алгоритм був успішно використаний в коді променевих траєкторій, який застосовувався для дослідження ІЦР-нагріву плазми в токамаці типу JET.